2013
DOI: 10.1111/ijfs.12212
|View full text |Cite
|
Sign up to set email alerts
|

Mango wine aroma enhancement by pulp contact and β‐glucosidase

Abstract: This study determined the influence of pulp maceration and b-glucosidase on mango wine physico-chemical properties and volatile profiles. The distinction in pH, sugars and organic acids among different treatments was not statistically significant. All wine samples reached around 8% (v/v) ethanol from about 16% (w/v) of sugars. The wine with pulp contact contained about ten times higher a-terpinolene and up to three times higher acetate esters than the wine without pulp contact, but mitigated the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Furthermore, the enzyme-treated wines had higher concentrations of both ethyl octanoate and isoamyl acetate than the nonenzyme-treated wines, which is consistent with the quantities of octanoic acid and n-decanoic acid between the two kinds of wines. The results indicated that the production of fatty acids has the positive correction with the production of ethyl esters, which is in agreement with other report by Li et al [24]. In Table 2, it could be found that pectase treatment could enhance eugenol, which is main wine flavor.…”
Section: 2supporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the enzyme-treated wines had higher concentrations of both ethyl octanoate and isoamyl acetate than the nonenzyme-treated wines, which is consistent with the quantities of octanoic acid and n-decanoic acid between the two kinds of wines. The results indicated that the production of fatty acids has the positive correction with the production of ethyl esters, which is in agreement with other report by Li et al [24]. In Table 2, it could be found that pectase treatment could enhance eugenol, which is main wine flavor.…”
Section: 2supporting
confidence: 91%
“…The nonextracted wines had significantly higher concentrations of isoamyl alcohol and phenylethyl alcohol than the extracted wines. There was statistically significant difference between the concentrations of alcohols after extraction, including 1-propanol, isobutyl alcohol, Isoamyl alcohol, 3-hexen-1-ol, 2,3-butanediol, alphaterpineol, phenylethyl alcohol, and 3-ethyl-1-butanol, which could be related to the higher availability of relative amino acids in pulpy juice [24].…”
Section: 2mentioning
confidence: 92%
“…Also, the use of exogenous β-glucosidase in mango pulp maceration and juice fermentation led to the enhancement of mango wine aroma, shown by higher levels of fatty acids and their ethyl esters, without affecting pH, sugars and organic acid content significantly. The addition of β-glucosidase could accelerate the release of terpenols, acetate esters, benzene derivatives and C13-norisoprenoids odour active volatiles and was found to be effective in intensification, diversification and balancing of mango wine aroma profile (Li, Lim, Yu, Curran, & Liu, 2013).…”
Section: Mango (Mangifera Indica L)mentioning
confidence: 99%
“…Other examples of grape berry-derived aglycones that contribute to flavour include terpenolds, C13-norisoprenoids and benzene derivatives [12]. These examples elicit mostly pleasant aromas that contribute to the aroma profile and have a low perception threshold [13].…”
Section: Introductionmentioning
confidence: 99%
“…Acid hydrolysis of glycosides occurs at a slow rate and may induce terpenol rearrangements [13,15]. Thermal hydrolysis has the potential to increase the breakdown of glycosides by 33%; however, high temperatures can also rearrange the natural structure of the glycosides [16].…”
Section: Introductionmentioning
confidence: 99%